Serological and molecular studies on Dirofilaria immitis in dogs from Turkey - Simsek, S.; Utuk, A. E.; Koroglu, E.; Rishniw, M. (Cambridge Univ Press, 2008)
We estimated the prevalence of Dirofilaria immitis infection in domestic dogs in five Turkish provinces - Sakarya, Kocaeli, Ankara, Elazig and Mersin - using a commercial ELISA kit for detecting circulating antigen and a PCR test for detecting circulating microfilarial DNA. A total of 211 whole-blood and serum samples were collected from dogs of various breeds, ages and life status (owned or stray). Sample population characteristics were recorded and examined for differences in prevalence. Additionally, we collected 15 blood samples from cats (14 owned and I stray) from Ankara province and used PCR to detect D. immitis infection. Twenty-seven (12.8%) of 211 dog samples were positive for D. immitis antigen by ELISA. No differences in prevalence were observed by sex (female: 14.4%; male: 10.7%; P > 0.05). The prevalence of D. immitis infection varied with age: 11.8% in younger dogs (0.5-2 years) and 17.5% in older dogs (3-5 years). Prevalence between stray dogs (15.2%) and owned dogs (9.3%) did not differ (P > 0.05). Prevalence rates were highest in Kocaeli province (18.3%), followed by Ankara (14.8%), Sakarya (12.3%) and Mersin (10.5%) provinces. Prevalence in Elazig province was 0%. No dogs or cats had microfilarial DNA detectable by PCR.
Keywords: Polymerase-Chain-Reaction; Canine Dirofilariasis; Heartworm Infection; Domestic Dogs; Prevalence; Seroprevalence; Korea; Spain